Evaluation of Soluble Human Leukocyte Antigen-G (sHLA-G) Isoforms and Regulatory T Cells in Relapsing-Remitting Multiple Sclerosis - Alsahebfosoul, Fereshteh; Zavaran Hosseini, Ahmad; Salehi, Rasoul; Etemadifar, Masood; Esmaeil, Nafiseh; Jamshidian, Azam (Iranian journal of allergy, asthma, and immunology, 2015)
Soluble forms of nonclassical human leukocyte antigen (HLA)-G have recently been suggested as immunomodulatory factors in multiple sclerosis (MS). HLA-G inhibits the effecter function of T cells and natural killer (NK) cells. Also regulatory T cells (Treg) are considered as pivotal players in MS pathogenesis. Thus, we aimed to evaluate the presence of HLA-G molecules and Treg cells in Relapsing-Remitting Multiple Sclerosis (RRMS) patients and compare it to healthy controls. Patients with RRMS (n=205, mean age=31.32±8.53) and healthy subjects (n=205, mean age=32.2±7.48) were studied. The patients subgrouped to untreated and treated with Interferon beta. Then sHLA-G levels (sHLA-G1 and sHLA-G5) were measured using ELISA method. Treg (CD4+ CD25+ Foxp3+) cells in patients who had sHLA-G>10 U/ml were characterized by using flow cytometry. Our data showed that there was no significant differences between RRMS patients and healthy controls in sHLA-G concentration (p>0.05). Treg cell frequencies were higher in the patients who had sHLA-G >10 U/ml compared to healthy subjects (p<0.05). Collectively, there was significant correlation between sHLA-G and frequency of Treg cells in treated RRMS patients and healthy individuals. It seems that high level sHLA-G has been instrumental in raising frequency of Treg cells in treated patients and could be associated with remission of MS disease.